4, 4″‐Disubstituted Terpyridines and Their Homoleptic FeII Complexes. Issue 19 (16th May 2013) - Harzmann, Gero D.; Neuburger, Markus; Mayor, Marcel
Abstract: A novel synthetic route to 4, 4″‐disubstituted‐2, 2′:6′, 2″‐terpyridine ligands by Suzuki–Miyaura cross‐coupling was elaborated by synthesizing compounds4a –5c . The considerable stability of 4‐substituted lithium triisopropyl 2‐pyridylborates2a –c, which are less prone to protodeboronation than similarly functionalized neutral boronic acid derivatives, enabled this synthetic route. The terpyridine core structure was further functionalized by exposing 4, 4″‐dichloroterpyridine (4b ) to Suzuki coupling conditions to yield 4, 4″‐diarylterpyridines5a –c . Homoleptic Fe II complexes8a –f of the reported terpyridine ligands were formed quantitatively, which demonstrates the lack of steric repulsion of substituents at the 4‐ and 4″‐positions during complexation. The solid‐state structures of particular ligands and Fe II complexes were analyzed by single‐crystal X‐ray crystallography. UV/Vis absorption data for the Fe II complexes are also provided to complement the results reported here. Abstract : A novel synthetic route to terpyridine ligands is reported. Pyridine building blocks are interlinked by Suzuki–Miyaura cross‐coupling reactions. The potential of the method is demonstrated by assembling the 4, 4″‐disubstituted terpyridine ligands shown, which are subsequently converted into their homoleptic Fe II complexes.